Do people living in rural and urban locations experience differences in harm when admitted to hospital? A cross-sectional New Zealand general practice records review study - Atmore, Carol (BMJ Open, 2021)
OBJECTIVE: Little is known about differences in hospital harm (injury, suffering, disability, disease or death arising from hospital care) when people from rural and urban locations require hospital care. This study aimed to assess whether hospital harm risk differed by patients’ rural or urban location using general practice data. DESIGN: Secondary analysis of a 3-year retrospective cross-sectional general practice records review study, designed with equal numbers of rural and urban patients and patients from small, medium and large practices. Hospital admissions, interhospital transfer and hospital harm were identified. SETTING: New Zealand (NZ) general practice clinical records including hospital discharge data. PARTICIPANTS: Randomly selected patient records from randomly selected general practices across NZ. Patient enrolment at rural and urban general practices defined patient location. OUTCOMES: Admission and harm risk and rate ratios by rural-urban location were investigated using multivariable analyses adjusted for age, sex, ethnicity, deprivation, practice size. Preventable hospital harm, harm severity and harm associated with interhospital transfer were analysed. RESULTS: Of 9076 patient records, 1561 patients (17%) experienced hospital admissions with no significant association between patient location and hospital admission (rural vs urban adjusted risk ratio (aRR) 0.98 (95% CI 0.83 to 1.17)). Of patients admitted to hospital, 172 (11%) experienced hospital harm. Rural location was not associated with increased hospital harm risk (aRR 1.01 (95% CI 0.97 to 1.05)) or rate of hospital harm per admission (adjusted incidence rate ratio 1.09 (95% CI 0.83 to 1.43)). Nearly half (45%) of hospital harms became apparent only after discharge. No urban patients required interhospital transfer, but 3% of rural patients did. Interhospital transfer was associated with over twice the risk of hospital harm (age-adjusted aRR 2.33 (95% CI 1.37 to 3.98), p=0.003). CONCLUSIONS: Rural patient location was not associated with increased hospital harm. This provides reassurance for rural communities and health planners. The exception was patients needing interhospital transfer, where risk was more than doubled, warranting further research.